Serum leptin concentration and advanced gastrointestinal cancers: a case controlled study - (:unkn) unknown (BMC, 2004)
Background: Serum leptin level is associated with appetite and energy expenditure in healthy individuals. We aimed to evaluate the serum leptin concentration and the other factors which may be associated with weight loss in patients with advanced gastrointestinal cancer. Methods: Forty-four patients with advanced gastrointestinal cancer (25 gastric and 19 colorectal cancer) and 25 healthy controls were enrolled. Serum leptin levels were measured as ng/ml via enzyme linked immuno-sorbent assay (ELISA) method in all subjects. The difference in serum leptin concentration between cancer and control group, the factor associated with its serum level and the relationship between serum leptin concentration and weight loss was evaluated. Results: Serum leptin concentration of cancer group was significantly lower than controls (p = 0.002). Female subjects had significantly higher serum leptin concentration than male subjects in control group (p = 0.01), while not in cancer group (p > 0.05). Serum leptin concentration was significantly related with gender in controls (p = 0.023, beta = 0.479), while no gender difference was observed in cancer group ( p > 0.05). No relationship was found between serum leptin concentration and weight loss percentage in cancer group in linear regression analysis (p > 0.05). No significant difference was observed in serum leptin concentrations between colon and gastric cancer sub-groups (p > 0.05). Conclusion: Independently from the site of gastrointestinal tract, serum leptin concentration in advanced gastrointestinal cancer is lower than controls and it is not a determinant factor in weight loss. In contrast to healthy subjects, gender does not effect the serum leptin concentration in patients with advanced gastrointestinal cancer.
Keywords: WEIGHT-LOSS; INFLAMMATORY RESPONSE; INTERLEUKIN-6; EXPRESSION; OBESITY; BREAST; LUNG